Physiotherapy Management of Frozen Shoulder EC Tendinitis Muscle Rotator Cuff Conditions Using Short Wave Diathermy, Active Resisted Exercise and Codman Pendular Exercise - Harunnurrasyid, Harunnurrasyid (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2020)
Background: Frozen shoulder is a pain in shoulders which conduces limitedness of shoulder joint motion. Tendinitis in M.Rotator Cuff, is an inflammation occured in muscle tendons fused in Rotator Cuff. Physiotherapy problematics of Frozen Shoulder are the existence of pain, the limitedness of joint motion, the decline of muscle strength, and the interference of functional activity. Physiotherapy examination includes examining pain with Verbal Descriptive Scale (VDS), examination of Limited Range Of Motion with Goneometer, examination of muscle strength with Manual Muscle Testing (MMT), and inspection of daily functional activities with the Shoulder Pain And Disability Index (SPADI) index. In this case, the chosen technology to resolve these problems are by using the modality of Short Wave Diathermy (SWD), Active Resisted Exercise and Codman Pendular Exercise. Objective: To know the effect of Physiotherapy Management Frozen Shoulder e.c Tendinitis Muscle Rotator Cuff conditions with Short Wave Diathermy (SWD), Active Resisted Exercise and Codman Pendular Exercise. Methods: This research was done in RSUD Kraton Pekalongan with analytic descriptive research design. Research subject in this Scientific Writing was a patient with Frozen Shoulder condition e.c. Tendinitis M.Rotator Cuff who was given physiotherapy interventions with the modality of Short Wave Diathermy (SWD), Active Resisted Exercise and Codman Pendular Exercise. Method of data collection and data analysis of this research were by using Autoanamnesis method. Research instruments consisted of the examination of pain, joint motion, muscle strength, and potentiality of functional activity. Result: After four times in therapy, the researcher got four result. They are there was a decline of force pain in T3 = 3 and motion pain in T2 = 2, there was an enhancement of joint motion in T3 and T4 in flexion movement, abduction, exorotation and endorotation of the left shoulder to active and passive movement, there was an enhancement of muscle strength in T3 = Muscle group exorotator and endorotator, and there was an enhancement of functional activity in T3. Conclution: a physiotherapy intervention with device modality and therapeutic exercise modality of can help reduce the problems arising on the conditions of Frozen Shoulder.